A frequency scalable coding scheme employing pyramid and subband techniques - Tan, T.K.; Pang, K.K.; Ngan, K.N. (IEEE transactions on circuits and systems for video technology, 1994)
A flexible layered coding scheme using block-based DCT domain decimation has been simulated in software. A conditional replacement scheme which switches adaptively between the pyramid and subband approaches at the coefficient level was studied. Experimental results comparing the adaptive scheme against the pyramid approach show that this new approach increases the overall coding efficiency of the scalable coder by up to 1 dB.< >